Diagnostic value of anti-gp210 antibodies in primary biliary cirrhosis: a case-based review. (26th June 2013) - Valour, Florent; Durupt, Stéphane; Khenifer, Safia; Durieu, Isabelle
Abstract : Primary biliary cirrhosis (PBC) is an autoimmune liver disease characterised by chronic cholestasis usually associated with antimitochondrial antibodies. Moreover, several types of antinuclear antibodies have been associated with primary biliary cirrhosis. We describe an 83-year-old man, in whom the exploration of a chronic cholestasis led to the diagnosis of primary biliary cirrhosis despite negative antimitochondrial antibodies, regarding the presence of anti-gp210 antibodies. Found in 25% of patients, these antinuclear antibodies must be sought before a strong suspicion of primary biliary cirrhosis with antimitochondrial antibodies negative, as they are highly specific of the disease. They are generally associated with a more aggressive form of PBC.